Simplified Calculation of Technological Electric Power Consumption Value for Its Transportation - V. V. Pavlovets (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains a simplified calculation of technological electric power consumption for its transportation in the elements of power supply network while supplying one element of power network to several consumers. The simplified calculation provides similar results with the accurate one but it is not labour consuming and it permits to reduce number of calculation